2013
DOI: 10.1021/nn304376z
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Fluorescent Semiconducting Polymer Dots with Narrow Emissions and High Brightness

Abstract: Fluorescent semiconducting polymer dots (Pdots) have attracted great interest because of their superior characteristics as fluorescent probes, such as high fluorescence brightness, fast radiative rates, and excellent photostability. However, currently available Pdots generally exhibit broad emission spectra, which significantly limit their usefulness in many biological applications involving multiplex detections. Here, we describe the design and development of multicolor narrow emissive Pdots based on differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
204
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(212 citation statements)
references
References 17 publications
5
204
0
3
Order By: Relevance
“…[56,58] Dabei haben wir festgestellt, dass die Einzelpartikel-Helligkeit und die Zellmarkierungshelligkeit von P-Punkten um mehr als eine Grçßenordnung hçher sind als die von anorganischen Q-Punkten mit vergleichbaren Partikelgrçßen. [56,58] Außerdem haben wir mehrere einfache, aber doch leistungsstarke Ansätze zur Einführung von funktionellen Gruppen und der Steuerung der Oberflächenei- [56][57][58][59][60][61][62][63][64][65][66][67] Diese Entwicklungen haben einen Einstieg in die Nanobiotechnologie und Nanomedizin erçffnet und geben eine neue Richtung vor, die von den etablierteren Bereichen der konjugierten Polymere für optoelektronische Bauteile und konjugierte Polyelektrolyt-Biosensoren abweicht. Die überlegenen Eigenschaften der P-Punkte gegenüber denen anderer Fluoreszenzsonden sind die Grundlage für ihr Potenzial in Biologie und Medizin als sehr helle In-vitro-und In-vivo-Sonden.…”
Section: Einführungunclassified
See 1 more Smart Citation
“…[56,58] Dabei haben wir festgestellt, dass die Einzelpartikel-Helligkeit und die Zellmarkierungshelligkeit von P-Punkten um mehr als eine Grçßenordnung hçher sind als die von anorganischen Q-Punkten mit vergleichbaren Partikelgrçßen. [56,58] Außerdem haben wir mehrere einfache, aber doch leistungsstarke Ansätze zur Einführung von funktionellen Gruppen und der Steuerung der Oberflächenei- [56][57][58][59][60][61][62][63][64][65][66][67] Diese Entwicklungen haben einen Einstieg in die Nanobiotechnologie und Nanomedizin erçffnet und geben eine neue Richtung vor, die von den etablierteren Bereichen der konjugierten Polymere für optoelektronische Bauteile und konjugierte Polyelektrolyt-Biosensoren abweicht. Die überlegenen Eigenschaften der P-Punkte gegenüber denen anderer Fluoreszenzsonden sind die Grundlage für ihr Potenzial in Biologie und Medizin als sehr helle In-vitro-und In-vivo-Sonden.…”
Section: Einführungunclassified
“…[45][46][47][48][49][50][51][52][53][54][55] In unserer jüngsten Arbeit haben wir die erfolgreiche Bildung von P-Punkt-Biokonjugaten vorgestellt und deren außergewçhnliche Helligkeit im Vergleich zu kommerziell erhältlichen farbstoffmarkierten Antikçrpern und Q-Punkten mit vergleichbaren Partikelgrçßen nachgewiesen. [56][57][58][59][60][61][62][63][64][65][66][67]104] Zwar befinden sich diese halbleitenden Polymere als fluoreszierende Nanopartikel noch im Frühstadium der Entwicklung, sie haben aber bereits immenses Interesse geweckt. [40][41][42][43][44] Es gab beachtliche Bemühungen, vielseitige halbleitende Polymernanopartikel (eine kleine Untergruppe davon sind die P-Punkte) zu erzeugen, ihre Eigenschaften und Funktionen einzustellen und deren Leistung für biomedizinische Untersuchungen zu verbessern.…”
Section: Von Konjugierten Polyelektrolyt-biosensoren Zu Hydrophoben Punclassified
“…[5][6][7][8][9] Among numerous species of uorescent particles, conjugated polymer nanoparticles (CPNs), arouse great interest in terms of following charming characteristics: ultrahigh brightness, structural diversity, functional designability, excellent biocompatibility, good photostability and water dispersion stability, 10 thus efficiently avoiding the shortcomings of conventional uorescent dyes and Qdots. Although CPNs have been proposed and applied in biological eld for only a few years, in virtue of the excellent optical properties and water dispersion stability, conjugated polymer nanoparticles have become a research hotspot as a candidate for labelling materials, such as cellular labelling, [11][12][13] in vivo imaging, [14][15][16][17][18] biosensing, 19 drug delivery 20 and photodynamic cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with ordinary fluorescent material, the Pdots are prepared easily, low cost, low cytotoxicity, lack of heavy metal ions. These superior properties make them well-suited for widespread fields such as biological detection and imaging, various biosensing platforms and so on [23,[27][28][29]. Chiu et al reported various Pdots with controllable PL properties and applied them to cellular imaging and heavy metal ions analysis [30][31][32].…”
Section: Introductionmentioning
confidence: 99%